Uso de interação natural em simulador de procedimentos para treinamento no setor elétrico - Castro, Rafael Henrique Assis de (2015)
Procedure Simulators have been used in several areas to help the execution of various tasks. The use of an interface that facilitates the manipulation of the actions at different stages of execution of a task, in the context of the simulator, can be an important component to ease the use by the professionals. As the electricity sector consists of several high-risk procedures, there is a great need for the good training of their operators. Seeking to support this training, the work described here aims, design and implement the integration of natural interaction in procedure simulators for the electricity sector, conducting tests with volunteers of the sector. As a case study, scenarios already developed in ATreVEE 3D simulator were analyzed and a new version of the simulator was developed, called ATreVEE IN, this time using the Leap Motion Controller, a device used for tracking hands. The ATreVEE IN consists of virtual environments whose user interface is performed via gestural commands, using a virtual representation of the user's hands within the environment. After the development of the new version, the two simulators were tested by users of electrical engineering, using the application of questionnaires to collect data. With these data it was observed that both versions had satisfactory performance, showing a potential to aid training. And although the first version of the simulator have obtained better results than the version with natural interaction, it is believed that this occurs in part because of the lack of user experience with this type of device. Users who already have experience with gestural interaction performed better in executing the tasks with ATreVEE IN than other users.